Growth and Yield of Lettuce Plants (Lactuca sativa L.) with Alternative Nutrition to Subtitute AB Mix in Hydroponic Systems - Toheni, Fredrik; Mege, Revolson; Satiman, Utari (Universitas Negeri Manado, 2024)
The hydroponic system is modern agricultural cultivation with various planting media as a substitute for soil, so hydroponics is an agricultural activity that is carried out by using water as a medium for distributing nutrients. This research aims to determine the effect of alternative nutrition to substitute AB mix on the growth and yield of hydroponic lettuce (Lactuca sativa L.). The research method was an experiment in a completely randomized design(CRD), using 5treatments with 4 repetitions, namely P0 (control/with ABmix nutrition) of 700-800 ppm, P1 (800-900 alternative nutrients), P2 (900-1000 ppm alternative nutrients), P3 (1000-1100 alternative nutrients), P4 (1000-1200 alternative nutrients), were analyzed by one way ANOVA analysis with a significance level of 0.05. Parameters observed were plant height, number of leaves, root length, leaf width, and fresh weight. The results showed that providing alternative nutrition significantly affected plant height, leaf width, and fresh weight of lettuce (Lactuca sativa L.). With the best treatment of 900-1000 ppm with plant height 35-41 cm, number of leaves 15-17, leaf width 17-18 cm, and plant wet weight 120-209 grams, the lowest yield was in treatment P0 with plant height 30-33 cm. the number of leaves is 15-16, and the wet weight of the plant is 117-146 grams